MODEL ESTIMASI UNTUK EVAPOTRANSPIRASI DAN LENGAS TANAH: STUDI KASUS SUB DAS MANTING, JAWA TIMURESTIMATE MODEL FOR EVAPOTRANSPIRASI AND SOIL HUMIDITY:CASE STUDY AT MANTING WATERSHED IN EAST JAVA - Ahmad Bey; Laode Sabaruddin (Agromet, 2000)
Abstract is available in the full text (pdf format)